2023
DOI: 10.1017/pcm.2022.13
|View full text |Cite
|
Sign up to set email alerts
|

Genetic heterogeneity in cardiovascular disease across ancestries: Insights for mechanisms and therapeutic intervention

Abstract: Cardiovascular diseases (CVDs) are complex in their aetiology, arising due to a combination of genetics, lifestyle and environmental factors. By nature of this complexity, different CVDs vary in their molecular mechanisms, clinical presentation and progression. Although extensive efforts are being made to develop novel therapeutics for CVDs, genetic heterogeneity is often overlooked in the development process. By considering molecular mechanisms at an individual and ancestral level, a richer understanding of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 141 publications
0
2
0
Order By: Relevance
“…Previous suggestions showed that first-line antihypertensive regimens differed based on BP-lowering in black individuals, with a preference for calcium channel blockers or diuretics over angiotensin-converting inhibitors or angiotensin receptor blockers. This approach does not consider the need for combination therapy, particularly in fixed doses, for most adults with hypertension, which removes any difference across self-identified race [39].…”
Section: Addressing Resistant or Difficult-to-treat Hypertensionmentioning
confidence: 99%
“…Previous suggestions showed that first-line antihypertensive regimens differed based on BP-lowering in black individuals, with a preference for calcium channel blockers or diuretics over angiotensin-converting inhibitors or angiotensin receptor blockers. This approach does not consider the need for combination therapy, particularly in fixed doses, for most adults with hypertension, which removes any difference across self-identified race [39].…”
Section: Addressing Resistant or Difficult-to-treat Hypertensionmentioning
confidence: 99%
“…The latest developments to be clinically adopted by specialism have been reviewed for the launch of the journal. These articles highlight some of the greatest achievements of precision medicine to date, including within cardiology (Soremekun, 2023 ), neurodegenerative diseases (Tsoi et al, 2023 ), oncology (Chamba, 2023 ; McGough, 2023 ), mitochondrial medicine (Chinnery, 2022 ), and also more recent areas of study including blood type susceptibility from severe disease with COVID-19 (Ellinghaus, 2023 ).…”
Section: First Contentmentioning
confidence: 99%